Application and Implications of Setting Up A Power of Attorney Form To Impose Dependent Rights (SKMHT) Made In Front of Notaries In Banyumas Regency - Lita Wulandari (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2020)
The Form of Power of Attorney to Impose Dependent Rights (SKMHT) made by notary deed is stipulated in Article 96 paragraph (1) of the Head Regulation of the National Land Agency No. 8 of 2012 and Article 38 of the Law of the Notary Department No. 2 of 2014. This research aims to analyze the arrangements on the form of SKMHT made before notaries and to analyze the application and implications of SKMHT form arrangements made before notaries in the Banyumas Regency. This research uses normative juridical research methods with a statute approach and conceptual approach. The result of the research obtained is that the form of SKMHT with the proper notarial deed is as stipulated in Article 38 UUJN number 2 of 2014. Violation of the provision causes the notary deed to be degraded as a deed under hand (Article 41 UUJN No. 2 of 2014) and implicates its dependent rights to be invalid so that the creditor does not have a position of priority or precedence to the holder (Droit de preference).Keywords: Notary Deed, Power of Attorney Imposing Mortgage Rights (SKMHT), Mortgage Rights